Connecting past and future knowledge to develop strategies for managing nuclear knowledge. (14th July 2006) - Barroso, A.C.O.; Imakuma, K.
Modern organisations try to 'peek' into the future by assessing emerging technologies and new competencies that should shape the future of an enterprise's competitiveness and use the results to establish its strategy today. Governments should have similar concerns to establish medium and long term policies relative to Science, Technology, Innovation, Industrial Development, International Relations etc. Foresight studies are invaluable tools to build a knowledge base to support decision making in these areas. Results of three Brazilian foresight studies were analysed: one covering the whole C&T area and the two others focused on the nuclear area. In this way, the relevance of the nuclear knowledge topics within the framework of the Brazilian C&T landscape could be assessed. Specific results are highlighted to give insights about the actions needed to promote a more effective policy on nuclear technology developments.